Mohammad Omer Osman and autumn - Mohammed Omer Ibrahim; Hawkar Mohammed Rashid (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Autumn and Mohammed Omer Osman is the title of this study; trying to describe the reflection of autumn season in the poems of the poet. Apart from the introduction ‌‌and the result, the study includes two main parts; the first part of the project is about (The content of the new Kurdish poetry and the reflection of nature in the new Kurdish poetry and the value of autumn in the new Kurdish poetry). In the second part of the study, the practical aspects are described as follows (The description of the seasons of the year is based on the poems of Muhammad Omar Osman and the value of autumn by Mohammad Omar Osman. The most important conclusions that the researcher has reached in this context are that in the poet’s opinion there are only two seasons of the year (winter and autumn), Unlike many other poets, who paid great attention to the seasons: (Autumn and Spring). On the other hand, it was the two seasons, which became the main theme of his poems. The autumn season has also covered the poetry of the poet, that is why he was known as a (General of autumn) ‌.